Extraction process optimization of Ligusticum chuanxiong hort. and its cardiomyocyte-protective effects via regulation of Dvl-1/Akt/GSK-3β/Nrf2 - Ling-Yu Wang; Dan-Dan Tang; Ruo-Lan Li; Mei-Yan Li; Li-Sha He; Xu-Feng Pu; Shu-Ting Zhao (Arabian Journal of Chemistry, 2024)
Background: The traditional Chinese medicine Ligusticum chuanxiong Hort. (CHX) has been used in the management of heart disease, particularly myocardial ischemia (MI), but its related active constituents and mechanisms remain to be further explored. Methods: We analyzed the blood entry constituents of CHX by UPLC-Q-TOF-MS/MS. The protective effects of the constituents on cardiomyocytes were evaluated using isoproterenol (ISO)-treated H9c2 cells to screen for quality markers (Q-markers) of CHX. We used a single-factor and orthogonal experimental design to optimize the extraction process of CHX based on Q-markers. Then, ISO-treated rats were prepared for evaluation of the anti-MI effects of CHX extracts via echocardiography, electrocardiography (ECG), H&E staining, Masson staining, TUNEL staining, and transmission electron microscopy (TEM). Furthermore, the potential mechanisms of CHX in ISO-treated H9c2 cells were explored via western blot assays, flow cytometry analysis, and immunofluorescence assays. Results: A total of 7 blood entry constituents of CHX were identified. All 7 components had protective effects on H9c2 cells and were considered to be Q-markers of CHX. The optimal extraction parameters for CHX were as follows: extraction time, 1.5 h; solid–liquid ratio, 1:20; ethyl alcohol (EtOH) concentration, 80 %; and 3 extraction times. The ECG results showed that CHX could reduce ISO-induced ST segment elevation. Echocardiography revealed that CHX improved heart function and increased fractional shortening (FS) and ejection fraction (EF) in ISO-treated rats. H&E, Masson and TUNEL staining showed that CHX reduced inflammatory infiltration and cell necrosis in heart tissue and reduced cardiac tissue fibrosis and apoptosis. TEM analysis revealed that CHX decreased cardiomyocyte mitochondrial swelling and lipid droplet formation. The in vitro results showed that CHX can prevent apoptosis, protect the mitochondrial membrane potential (MMOP) and reduce oxidative stress in ISO-treated H9c2 cells. Western blot and immunofluorescence results indicated that the mechanism of the anti-MI effect of CHX was related to the regulation of the Dvl-1/Akt/GSK-3β/Nrf2 pathway. The cellular protective effect of CHX can be inhibited by Akt inhibitor MK-2206. Conclusion: Collectively, we optimized the extraction process of CHX, and the optimized CHX showed significant anti-MI effects via regulation of the Dvl-1/Akt/GSK-3β/Nrf2 signaling pathway.